Perancangan Digitalisasi Kampus Menggunakan Metode TOGAF - Buchory, Herry Achmad; Rusyandi, Deddy; Bachmid, Faiz Said (STIE Ekuitas, 2019)
Campus digitization is an effort to deal with the development of existing technology. STIE Ekuitas needs to deepen their business needs and evaluate technology resources and information systems, so that opportunities are obtained that can be utilized and developed by stakeholders involved in the organization. STIE Ekuitas is not enough just to have a business strategy to face competition. The business strategy as outlined in the business plan must be equipped with technology and information system strategies to make optimal use of information technology and systems. The system architecture design in the STIE Equitas TOGAF framework (The Open Group Architecture framework) is a framework for enterprise architecture that provides a comprehensive approach to planning, designing, and implementing an enterprise information architecture. The results of the research found that STIE Ekuitas does not have an enterprise architecture plan and information technology in STIE Ekuitas has not fully utilized in helping STIE Ekuitas activities incur non-economical costs for technology investment, The framework provides directions for the development of information systems that are needed Keywords: Campus Digititazion, Information System, TOGAF